Critical Literacy and Information Filtration: The Embodiment of the Rights and Obligations of Good Citizens - Leong Kin Heng; Violine Melvina; Ronaldo Zai (Punggawa Legacy Center, 2026)
Critical literacy and information filtration are essential in a democratic climate as a manifestation of the rights and obligations of good citizenship. Critical literacy and information filtration are essential for maintaining a healthy social order, free from news that is inconsistent with the facts. This research is crucial for every citizen to understand the importance of enhancing critical literacy and information filtration, especially in the context of Indonesia, which is undergoing a massive information dissemination process in the current technological era. This is essential for every citizen to be wise and responsible in disseminating and receiving information, both directly and digitally. This research uses a qualitative research method with a literature study data collection technique. The literature study was conducted through the stages of data collection, reduction, presentation, and drawing conclusions. The results of the study indicate the importance of enhancing critical literacy and information filtration in the current massive digital era. The importance of critical literacy and information filtration are important in maintaining the social order by prioritizing education as a good foundation so that every citizen can share or receive information well and wisely.